(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
Scientific and technical terminology is a very interesting area of vocabulary. In our time, when science and technology are rapidly developing in all spheres of human activity, issues of terminology are becoming especially relevant. The formation process of special field terms, as a rule, passes through two historical stages - spontaneous and organized and purposeful. If the first is related to the formation of a professional scientific mining industry, the second is related to its high level of development